(untitled) (Archives of Criminology, 2008)
This article discusses the role of the media in generating fear and spreading populism among the Polish public opinion. The author points out the mutual dependence of the world of politics and the media: on the one hand, the mass media follow the political line of the party that finances its activities; on the other hand, politicians succumb to the social moods generated by the media and introduce legislative changes under such pressure. The text explains the mechanism used by the fourth estate to arouse fear among the public. The media create the Other and identify it with social pathology and the source of danger, then political groups win the votes of voters with the promise of protectingthem from the Other. According to the author, such a phenomenon increases the process of criminalisation and penalisation. He also points to the multitude of amendments to the Penal Code in a short period. The article cites statistics on the decrease in crime between 2005 and 2007, which contradict the media messages calling for changes to the penal code due to rising crime. Filar presents a pattern of media coverage which promotes the belief that a given right (sensitive to the public good) is at risk. The media then publicise a single criminal case, thus stirring up fear and a sense of threat among the public. In response, politicians draft amendments to criminal law, making it more stringent, and then the parliament adopts them, often in an ill-considered manner. The text also includes examples of such amendments, as in the case of car theft or paedophilia. In conclusion, the author stresses the important role of the media in creating and encouraging legal populism, which in consequence leads to destabilisation and destruction of the law.